2011
DOI: 10.1095/biolreprod.111.091082
|View full text |Cite
|
Sign up to set email alerts
|

TRPC1, STIM1, and ORAI Influence Signal-Regulated Intracellular and Endoplasmic Reticulum Calcium Dynamics in Human Myometrial Cells1

Abstract: To explore the relationship between signal-stimulated increases in intracellular calcium ([Ca(2+)](i)) and depletion and refilling of the endoplasmic reticulum (ER) Ca(2+) stores ([Ca(2+)](L)) in human myometrial cells, we measured simultaneous changes in [Ca(2+)](i) and [Ca(2+)](L) using Fura-2 and Mag-fluo-4, respectively, in PHM1-41 immortalized and primary cells derived from pregnant myometrium and in primary cells derived from nonpregnant tissue. Signal- and extracellular Ca(2+)-dependent increases in [Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 54 publications
4
36
1
Order By: Relevance
“…The cell elasticity determines macrophage functions and is known to regulate phagocytosis or LPS responsiveness. In a positive feedback loop, the cytoskeleton can modulate the intracellular trafficking machinery through microtubules and calcium mobilization (59,60). This event may amplify such a phenomenon and explain the spontaneous release of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The cell elasticity determines macrophage functions and is known to regulate phagocytosis or LPS responsiveness. In a positive feedback loop, the cytoskeleton can modulate the intracellular trafficking machinery through microtubules and calcium mobilization (59,60). This event may amplify such a phenomenon and explain the spontaneous release of pro-inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in defining proteins associated with this process are consistent with that hypothesis. For example, depletion of endoplasmic reticulum Ca 2ϩ stores trigger endoplasmic reticulum sensors (STIM1 and -2), which send signals to the plasma membrane to activate two types of store operated Ca 2ϩ channels: Ca 2ϩ release-activated Ca 2ϩ (CRAC) channels, which are composed of Orai proteins, and STIMs (53, 54) as well as SOC channels, which incorporate Transient Receptor Potential Channels (55)(56)(57). In turn formation of STIM/Orai channels inhibits VGCCs and even leads to their internalization (53,54).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Mibefradil (8) is an inhibitor of T-type Ca 2+ channels, 27 and was briefly marketed for migraine, but was withdrawn because of drug-drug interactions due to its potent inhibition of CYP3A4. 28 In an earlier study 29 it was shown to have no effect on signal-and extracellular Ca 2+ -dependent increases in [Ca 2+ ] stimulated by oxytocin. In our assay both 7 and 8 were active (albeit not very potent; IC 50 s 67 and above 100 µM respectively) against Orai1-mediated Ca 2+ influx (Table 1) but were not selective with respect to inhibition of the Ca V 2.2 channel (data not shown).…”
Section: Biologymentioning
confidence: 96%